Macroeconomic factors that affecting youth unemployment in Malaysia - Evanezza Michael; Caroline Geetha (Penerbit UMS, 2020)
The purpose for this research was to identify the impact of the macroeconomic factors that is inflation rate, Gross Domestic Product (GDP) and Foreign Direct Investment (FDI) towards to youth unemployment in Malaysia. This research collects the data from Bloomberg and the data that have been collected will be Analyse using the Eviews software. The result of this research shows that inflation rate and GDP have a negative relationship with youth unemployment. Meanwhile for the FDI, it shows a positive relationship with youth unemployment. The researcher hopes that this research can help giving more information on the impact of macroeconomic factors towards youth unemployment in Malaysia. Lastly, the researcher also hopes that the problem of youth unemployment in Malaysia can be reduced by doing this research.